1985
DOI: 10.1128/iai.47.3.730-736.1985
|View full text |Cite
|
Sign up to set email alerts
|

Relative hydrophobicities of Actinomyces viscosus and Actinomyces naeslundii strains and their adsorption to saliva-treated hydroxyapatite

Abstract: The present study examined 42 strains ofAcfinomyces spp. to determine whether adsorption to saliva-treated hydroxyapatite (SHA) of the selected strains of this prominent group of dental-plaque bacteria correlated with hydrophobicity. The relative hydrophobicity of the strains was determined by their adsorption to hydrophobic gels (i.e., phenyl-Sepharose) and their aggregation in ammonium sulfate. Within serogroups the relative hydrophobicity for the strains was similar. The relative adsorption of strains to SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Following, generally, the HIC method described previously (Smyth et al 1978;Hermansson et al 1982), replicate seawater subsamples were passed, respectively, through preconditioned high-performance liquid chromatography preparatory columns (Waters) containing 100 mg of hydrophobic (C18) or hydrophilic (Diol) resin. A relative index of cellsurface hydrophobicity (HIC index) was then computed using the expression (Clark et al 1985)…”
Section: Methodsmentioning
confidence: 99%
“…Following, generally, the HIC method described previously (Smyth et al 1978;Hermansson et al 1982), replicate seawater subsamples were passed, respectively, through preconditioned high-performance liquid chromatography preparatory columns (Waters) containing 100 mg of hydrophobic (C18) or hydrophilic (Diol) resin. A relative index of cellsurface hydrophobicity (HIC index) was then computed using the expression (Clark et al 1985)…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobic interactions may contribute to the adhesion of viridans streptococci to oral surfaces in vitro (Nesbitt et al 1982;Hogg et al 1983;Clark et al 1985) and Svanberg et al (1984) have shown that relatively highly hydrophobic strains of Streptococcus mutans implant significantly better in human mouths than less hydrophobic strains of the same species.…”
mentioning
confidence: 99%
“…Therefore, our findings show that the cell surface of various non-encapsulated and encapsulated CN Staph strains is rather heterogeneous. It may be that strains with a high degree of cell surface similarity have been used in a number of studies reporting a rather good linear correlation between the SAT value and the bacterial adherence to octane [26] or to octylsepharose [19,27,28].…”
Section: Discussionmentioning
confidence: 99%